Four new Neotropical species in the Hirtodrosophila hirticornis species group (Diptera: Drosophilidae) - Junges, João; Robe, Lizandra Jaqueline; Gottschalk, Marco Silva (Zootaxa, 2019)
Hirtodrosophila Duda, 1923 (Diptera, Drosophilidae) is a worldwide genus associated with fungi that encompasses 30 Neotropical species. They are gathered into four clusters: glabrifrons species group (Burla 1956), hirticornis species group (Burla 1956), magnarcus species group (Frota-Pessoa 1951), and thoracis species group (Grimaldi 1987), although there are still some ungrouped species. Nevertheless, their species richness is highly underestimated, and several unknown species of the genus have been sampled in different Brazilian regions. The known Neotropical flies of the hirticornis group belong to a set of four yellow sibling species, which are very difficult to identify based only on external morphology, a fact that partially explains the knowledge gap regarding ecology, biology, and evolution of the group. However, these species are easily sampled around some fungi fruiting bodies, particularly over Auricularia spp. (Auriculariales, Auriculariaceae). In the last years, we collected some hundreds of specimens, which allowed us to detect some common but yet undescribed species. Thus, here we describe four new Neotropical species in the hirticornis group.